TORCH Re-activation Concomitant with Drug-induced Hypersensitivity Syndrome Shows Erythema Multiforme-like and Vasculitis Clinical Features - Budianti, Windy Keumala; Rihatmadja, Rahadi; Aulia, Izzah; Effendy, Isaak (UI Scholars Hub, 2022)
Background: Drug-induced hypersensitivity syndrome (DIHS) can be associated with cytomegalovirus (CMV) infection, besides induced by drugs. We report a case of DIHS with prolonged atypical clinical features and vasculitis precipitated by drug allergy, CMV, and other viral infections. Case illustration: A 54-year-old female presented with generalized follicular erythematous papules and waxy palmoplantar keratoderma since one month before admission. The symptoms started as a purpuric lesion on the upper extremities, spreading as erythematous papules on the trunk with facial edema, accompanied by fever and chronic cough. She had been previously treated with ambroxol and cephalosporin. Cutaneous drug allergy reaction was assessed. Although in therapy with systemic corticosteroids, lesions still appeared and became confluent, with new palpable purpura on the extremities. Histopathology showed interface dermatitis, consisting of lymphocytes and plasma cells but lacking eosinophils, leukocytoclastic vasculitis, and numerous dyskeratotic keratinocytes. The possibility of systemic infection was sought, and TORCH examination suggested acute and latent infection. The patient had a positive PCR for CMV. Intravenous ganciclovir 500 mg/day for three weeks and a low dose of systemic corticosteroids led to complete cessation of skin and pulmonary symptoms. Discussion: The clinical and histopathological examination was consistent with erythema multiforme. Therefore, high titer of IgM and IgG anti-CMV, and excellent response to ganciclovir supported our suspicion of an infection-induced process. The infection might be precipitated by a drug allergy. Conclusion: CMV-associated skin lesion could be precipitated by drug hypersensitivity, resulting in erythema multiforme-like clinical features with vasculitis. Severe systemic involvement related to CMV reactivation. Early anti-CMV therapy showed good improvement and reduce risk of mortality.